Application and validation of mortality functions to assess the consequences of flooding to people - Mauro, M. Di. (2013)
The assessment of potential consequences of a flood event to the exposed population is a key question for flood risk managers. This issue is increasingly a triggering research on assessing potential numbers of fatalities because of flooding. In the past, mortality functions were proposed to estimate the fatalities in areas that are exposed to a hazard because of flood defence failures-in the Netherlands. This paper describes a study undertaken to validate those mortality functions and assesses their applicability for appraising consequences of flooding to people in a UK-specific context. The functions were applied to the 1953 North Sea Storm and, in particular, to the Canvey Island that suffered from 58 fatalities as consequence of this flood event. This paper describes the results of this research and provides a review of the criteria used to apply the functions, as well as guidelines for applying these functions in a UK context.